2020
DOI: 10.3390/ijms21124563
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment Promotes Remote Hippocampal Plasticity after Experimental Cortical Stroke

Abstract: Cognitive impairment is common after stroke, and disturbances in hippocampal function are often involved, even in remote non-hippocampal injuries. In terms of hippocampal function, growth hormone (GH) is known to affects plasticity and cognition. We aimed to investigate whether GH treatment after an experimental cortical stroke could enhance remote hippocampal plasticity and the hippocampal-dependent visual discrimination task. C57BL6 male mice were subjected to cortical photothrombotic stroke. Stroke mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 67 publications
1
33
0
1
Order By: Relevance
“…Although promising, the use of individual pharmacological strategies e.g., donepezil and memantine, have a patchy record of success ( 2 ). Recent evidence has shown pro-cognitive effects of exogenously delivered growth hormone post-stroke ( 6 9 ). Another equally promising pro-cognitive therapy has been the use of intermittent exposure to a reduced oxygen environment ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although promising, the use of individual pharmacological strategies e.g., donepezil and memantine, have a patchy record of success ( 2 ). Recent evidence has shown pro-cognitive effects of exogenously delivered growth hormone post-stroke ( 6 9 ). Another equally promising pro-cognitive therapy has been the use of intermittent exposure to a reduced oxygen environment ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endogenous GH/IGF-I axis or exogenously administered GH or IGF-I act in neuroprotection, neurogenesis, angiogenesis, and synaptogenesis [ 22 , 34 , 35 , 36 , 37 , 38 , 39 ], as well as modulate neurotransmission through the synuclein (SYN) signal [ 36 ] and increases key mechanisms for a series of brain functions [ 28 , 37 , 38 , 39 ] and brain repair after an injury [ 34 , 36 , 37 ]. These reasons led to the use of GH or IGF-I in different models of brain injuries [ 34 , 35 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Regardless of the fact that TBI can produce GH-deficiency (GHD) [ 42 ], which contributes to the cognitive sequelae associated with TBI [ 43 ], and GH treatment in rats after TBI improves their cognitive, motor and behavioral activities [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these effects reduce the symptoms caused by TBI and provide cognitive improvements [ 9 , 46 , 47 ], motor improvements, beneficial behavioral and psychological effects (reduces anxiety, depression, sleep disorders) and improves quality of life [ 48 , 49 ]. These positive results can be seen in both the short and long term and are like those seen with GH treatment in ischemia and stroke [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously reported on the use of the rodent touchscreen platform to assess cognitive decline in mice after photothrombotic stroke 18 20 . We demonstrated that the rodent touchscreen platform constitutes a pertinent assessment tool which is sensitive to the effects of pharmacological/therapeutic interventions to improve cognitive function after stroke 19 21 . The major question that we wanted to address was “do mice and humans in the chronic phase post-stroke respond similarly when evaluated using touchscreen delivered PAL task?” The aim of the present study was to apply and in parallel evaluate the touchscreen-based visuospatial object-location PAL task in chronic stroke survivors and in mice in chronic phase after experimental stroke.…”
Section: Introductionmentioning
confidence: 99%